The Influence of Participative Leadership and Work Motivation on Employee Innovation - Nursilawati, Devi; Aulia, Nur Fitri (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
This study aims to analyze the influence of participative leadership and work motivation on employee innovation. Participative leadership is defined as a leadership style where leaders involve employees in decision-making and encourage active participation in work processes. Work motivation refers to the internal and external drives that affect employees' enthusiasm, commitment, and performance. Employee innovation is the ability of employees to generate new ideas, creative solutions, and improvements in work processes. The research method used is a quantitative survey with a sample consisting of employees from various companies in the manufacturing sector. Data were collected through a questionnaire that has been tested for validity and reliability. Data analysis was performed using multiple linear regression to examine the relationship between participative leadership, work motivation, and employee innovation. The results of the study show that participative leadership and work motivation have a significant positive effect on employee innovation. These findings indicate that involving employees in decision-making and providing high motivation can enhance their ability to innovate. This research provides practical implications for company management to adopt a participative leadership style and enhance motivational factors to encourage employee innovation.